Back pain in adolescents and young people of the Republic of Tuva, associations with internet addictive behavior - Evert, Lydia S.; Grishkevich, Natalia Yu.; Bakhshieva, Svetlana A.; Sat, Diana A. (The New Research of Tuva, 2024)
The article analyzes the prevalence and structure of back pain (dorsalgia) among adolescents and young adults living in the Republic of Tuva, Russia. The problem relates to the specific features of online behavior and the content consumed on the internet. Nonspecific back pain is a significant and widespread health issue among adolescent and young populations in many countries worldwide. The importance of this issue is due to its frequent association with pathological internet use. The conclusions of the study are based on the analysis of the results from online testing among Tuvan adolescents and young people. The surveys were conducted through random sampling between January 2023 and January 2024, and 2,853 participants completed a screening questionnaire as well as three psychometric instruments: the CIAS Internet Addiction Scale, questionnaires to verify dependence on social media and gaming, and dependence on smartphones. A comparative analysis of online behavior and internet content indicators in groups that differ in gender, ethnicity (Tuvan and Russian), and the presence or absence of dorsalgia is presented. The analysis found that there was a higher prevalence of pathological (21.6% vs. 8.8%) and maladaptive internet use (50.7% vs. 41.8%) among individuals with dorsalgia compared to those without. The direction of change in these indicators was similar among Tuvans and Russians, regardless of whether they had dorsalgia or not. Russians and representatives of the Tuvan ethnic group with dorsalgias (back pain) of different localization were characterized by a higher frequency of dependence on computer games and social networks, as well as mixed Internet addiction. Tuvans with back pain were also more likely to be characterized by undifferentiated internet addiction and smartphone addiction compared to their Russian peers. No significant gender differences were found in the analyzed indicators among the groups with and without dorsalgia.